Hubungan antara Psychological Capital dengan Authentic Leadership pada Entrepreneur Usaha Kecil di Jakarta Timur - Noor Isti Mahardini; Iman Sukhirman (Fakultas Psikologi Universitas Pancasila, 2010)
The main objective of this study was to analyze the relationship between psychological capital and authentic leadership among small-scale entrepreneurs in East Jakarta. The study used quantitative approach and field study design. Respondents involved in this study were 111. Pearson's correlations statistics which was applied to analyze the data yielded correlation coefficient 0.405 with significant value 0.000 (p<0.01). This demonstrated a positive and significant relationship between psychological capital and authentic leadership among the small-scale entrepreneurs in East Jakarta. In short, the higher psychological capital, the greater authentic leadership, and the other way around.